China-Angola relationship with reference to the construction sector - Ata, Philippe Asanzi Mbey (My University, 2009)
ABSTRACT The People‟s Republic of China first developed an interest in Africa during the late 1950‟s, a few years after the end of the Chinese civil war. Chinese interests in Africa occurred at a time when the Communist regime led by Chairman Mao Tse-Tung was facing serious threats from the United States of America (US) and its allies. As such, the objective of China‟s policy on Africa at the time was to seek the support of African countries in a bid to resist isolation from the US and its allies as well as to foster revolutions in Africa aimed at depriving the West of African‟s raw materials and access to African markets. During the 1970‟s, China‟s policy on Africa changed significantly as the result of China‟s admission into the UN and the relative success achieved by that country in getting recognition from African countries. Consequently, China‟s policy on Africa became less aggressive toward the West. During the 1980‟s, the normalisation of China‟s relations with the US as well as the arrival of new leadership in China, prompted the country to adopt a foreign policy centred on economic development. As such, Africa became less important for China. Over the last two decades China has achieved a robust economic growth that averaged 9.5%. In order to sustain its formidable economic growth, China needs access to raw materials, notably oil and minerals. Therefore, in the beginning of this new century China renewed its interest in Africa. Nevertheless, compared to the 1950‟s when China‟s interest in Africa was mainly driven by ideological factors, the current strong Chinese interest in Africa is driven by economic factors, namely, access to African oil and minerals. This study investigates the partnership between China and Angola, with a particular interest on the impact of trade between China and Angola and Chinese investments on the Angolan economy as well as on the Angolan population. Concerning Chinese investments in Angola, this study focuses on the Angolan construction sector. This study attempts to gauge whether Chinese involvement in Angola is a positive factor for the country‟s economic development given the fact that Chinese involvement in Angola is not altruistic.